2019
DOI: 10.1038/s41598-018-36976-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of epileptic brain states by dynamic functional connectivity analysis of simultaneous EEG-fMRI: a dictionary learning approach

Abstract: Most fMRI studies of the brain’s intrinsic functional connectivity (FC) have assumed that this is static; however, it is now clear that it changes over time. This is particularly relevant in epilepsy, which is characterized by a continuous interchange between epileptic and normal brain states associated with the occurrence of epileptic activity. Interestingly, recurrent states of dynamic FC (dFC) have been found in fMRI data using unsupervised learning techniques, assuming either their sparse or non-sparse com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Although unreported so far, the match between dFC states derived from fMRI and EEG data found in the present study was somewhat expected, considering that a number of studies have already found EEG correlates of dFC fluctuations and brain states measured with simultaneous fMRI (Tagliazucchi and Laufs, 2015), motivated by the yet unclear physiological underpinnings of dFC (Thompson, 2018). These studies were mainly focused on healthy subjects (Chang and Glover, 2010;Allen et al, 2017) and epilepsy patients (Laufs et al, 2014;Lopes et al, 2014;Preti et al, 2014;Omidvarnia et al, 2017;Abreu et al, 2019). Interestingly, when comparing the contrast of interest for mapping the FEPN with the contribution over time of each fMRI and EEG dFC state, we found that the contribution of two matched dFC states based on their spatial correlation were significantly correlated with the FEPN contrast.…”
Section: Dynamic Functional Connectivity and Brain Statessupporting
confidence: 68%
See 4 more Smart Citations
“…Although unreported so far, the match between dFC states derived from fMRI and EEG data found in the present study was somewhat expected, considering that a number of studies have already found EEG correlates of dFC fluctuations and brain states measured with simultaneous fMRI (Tagliazucchi and Laufs, 2015), motivated by the yet unclear physiological underpinnings of dFC (Thompson, 2018). These studies were mainly focused on healthy subjects (Chang and Glover, 2010;Allen et al, 2017) and epilepsy patients (Laufs et al, 2014;Lopes et al, 2014;Preti et al, 2014;Omidvarnia et al, 2017;Abreu et al, 2019). Interestingly, when comparing the contrast of interest for mapping the FEPN with the contribution over time of each fMRI and EEG dFC state, we found that the contribution of two matched dFC states based on their spatial correlation were significantly correlated with the FEPN contrast.…”
Section: Dynamic Functional Connectivity and Brain Statessupporting
confidence: 68%
“…Such window lengths were selected based on a recent meta-analysis revealing that physiologically meaningful, and statistically validated dFC fluctuations can be detected on the fMRI when using a window length between 30 and 60 s (Preti et al, 2017). Additionally, our previous study focused on the detection of epileptic dFC states from simultaneous EEG-fMRI data also showed the ability to detect epileptic dFC states irrespective of the window length within the abovementioned interval (Abreu et al, 2019). With this combination of parameters, comparable properties are expected to be captured on fMRI and EEG-ESI dFC data, while guaranteeing that all points at the end of the dFC data are considered when building the respective last sliding windows.…”
Section: Dynamic Functional Connectivity Analysis Estimation Of Dfcmentioning
confidence: 99%
See 3 more Smart Citations